The Feasibility, Reliability, and Validity of Using the Self-report Version of interRAI Check-Up Among Community Dwelling Older Adults - Iheme, Linda Ogechi (University of Waterloo, 2019)
As the result of population aging around the world, the prevalence of chronic conditions is increasing. Early detection through constant monitoring is an effective strategy of minimizing the impact of chronic conditions on morbidity and mortality. However, clinician administered assessments are often not routinely completed nor done for the entire population because they require resources that may not be available. A self-report tool that can be administered by older adults and their caregivers could help achieve broader surveillance at minimal cost and contribute to enhancement of chronic disease management globally. In the meantime, as the population of cultural minorities in Canada is increasing, it will be important to examine the feasibility and acceptability of using self-report interRAI Check-Up (CU) assessment tool among older adults from different backgrounds. The study compared the experiences of older adults who electronically completed the assessment tool entirely by themselves with approaches involving the help of a lay interviewer or their informal caregiver. Also, this study evaluated the reliability and validity of data collected with self-report CU. This study concluded that CU was optimally accepted by older adults in this study. Also, the internal consistency and validity of data collected with CU is comparable to data collected by trained health professionals in Ontario using the RAI-HC among home care population.
Keywords: aging; older adults; interRAI; check-up; assessment